The role of gut microbiota in infectious diseases. Issue 4 (2nd January 2022) - Cai, Yongjie; Chen, Lingming; Zhang, Sien; Zeng, Lingchan; Zeng, Gucheng
Abstract: The intestine, the largest immune organ in the human body, harbors approximately 10 13 microorganisms, including bacteria, fungi, viruses, and other unknown microbes. The intestine is a most important crosstalk anatomic structure between the first (the host) and second (the microorganisms) genomes. The imbalance of the intestinal microecology, especially dysbiosis of the composition, structure, and function of gut microbiota, is linked to human diseases. In this review, we investigated the roles and underlying mechanisms of gut microecology in the development, progression, and prognosis of infectious diseases. Furthermore, we discussed potential new strategies of prevention and treatment for infectious diseases based on manipulating the composition, structure, and function of intestinal microorganisms in the future. This article is categorized under: Infectious Diseases > Molecular and Cellular Physiology Abstract : The role of gut microbiota in the prevention and treatment of infectious diseases.